(Invited) Defects and Dopants in Silicon and Germanium Nanowires. (8th September 2015) - Fanciulli, Marco; Belli, Matteo; Paleari, Stefano; Lamperti, Alessio; Molle, Alessandro; Sironi, Mauro; Pizio, Antonio
Abstract : The current status of the investigation of defects in silicon and germanium nanowires and at the interface between the group IV semiconductor and its oxide in 1D nanostructures is reviewed and discussed. The paper concentrates on nanowires produced by metal assisted chemical etching for silicon and by the vapor-liquid-solid (VLS) growth method for germanium. For silicon nanowires the role of defects at the interface between the semiconductor and its oxide and of hydrogen in passivating donor atoms is addressed. The experimental data on germanium nanowires are scarce and we report here only evidence of dislocations.